1991
DOI: 10.1073/pnas.88.11.4596
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activities in four different forms of human immunodeficiency virus 1 pol gene products.

Abstract: 4596The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. §1734 solely to indicate this fact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Hu & Kang (1991) reported that many forms of artificial HIV pol gene products, including partly cleaved forms, possessed RT activity in activity gels. However, using activity gel analysis of HIV RT, Starnes et al (1988) demonstrated that p66 was the only polypeptide expressing HIVspecific DNA polymerase activity in infected H9 cells, and interpreted this polypeptide species as being derived from both intracellular RT and budded but trapped virions.…”
Section: Discussionmentioning
confidence: 99%
“…Hu & Kang (1991) reported that many forms of artificial HIV pol gene products, including partly cleaved forms, possessed RT activity in activity gels. However, using activity gel analysis of HIV RT, Starnes et al (1988) demonstrated that p66 was the only polypeptide expressing HIVspecific DNA polymerase activity in infected H9 cells, and interpreted this polypeptide species as being derived from both intracellular RT and budded but trapped virions.…”
Section: Discussionmentioning
confidence: 99%
“…The pJV.PR-RT,B.COLL expression vector contains a COLL mutation which replaces the Leu-Thr residues of the PR-RTcx cleavage site with the consensus cleavage site for collagenase, Pro-Leu-Gly-Pro. Symbols: 0 of human immunodeficiency virus (HIV) (22). The recombinant proteins undergoing specific proteolysis all have Gag sequences upstream of the PR domain.…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of these results is further complicated by the observations that different methods of purification (metal chelate or ion-exchange chromatography) or expression (bac-VOL. 67, I1993 on July 6, 2020 by guest http://jvi.asm.org/ Downloaded from 7594 STEWART AND VOGT teria or insect cells) can drastically affect the level of RT activity of HIV PR-RT (22,33). In the pararetrovirus cauliflower mosaic virus, RT was reported to be inactive as a PR-RT fusion (55) but active when the amino-terminal PR domain (56) was proteolytically removed (54) or genetically deleted (55).…”
Section: Discussionmentioning
confidence: 99%
“…feet the RT activity. 11,[13][14][15][16][17][18][19] The RT activity in these cells is between 10-and 20-fold higher than in the HT-1080 parental cell line and is stable for at least 30 cell generations, even in the absence of G418 selection. Indirect immunofluorescence of the cells revealed cytoplasmic localization of the expressed RT subunits.…”
Section: Localization Of Reverse Transcriptase Expressionmentioning
confidence: 99%
“…All other studies have depended on bacterial, yeast, or insect cell expression systems, none of which allow the longterm intracellular study of RT. [12][13][14][15][16][17][18][19][20][21][22] In this study the expression of HIV-1 RT in the presence or the absence of PR expression in the HT-1080 human fibrosarcoma cell line was investigated. The RT activity associated with the individual subunits was also examined.…”
Section: Introductionmentioning
confidence: 99%